What are they saying about the parables? - Gowler, David B. 1958- (New York Mahwah, NJ Paulist Press, 2021)
"A wonderful addition to the unique and well-respected WATSA series, introducing current scholarly thinking about the parables of Jesus, a creative and dynamic area in New Testament studies"--
Includes bibliographical references
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jesus Christ -- Parables